Flexicurity in Belgium : a proposal based on economic principles - Bart Leo Wim Cockx; Bruno van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2009)
The current unemployment insurance and employment protection legislation were set up in an environment in which relationships between workers and firms were typically long-lasting and stable. The increasing globalisation of the economy and the rapid technological and organisational changes require more flexibility leading to career paths which are much more volatile both within and between firms. Current institutions must be therefore urgently reformed to reconcile this new need of more flexibility with that of security for workers. Rather than proposing a reform on the basis of existing institutions abroad, we propose a reform that is explicitly guided by economic principles.
Keywords: H11; H21; H23; J65; J68; 330; flexicurity; employment protection; unemployment insurance; active labour market policies; optimal design; Flexicurity; Arbeitsmarktflexibilisierung; Soziale Sicherung; Sozialreform; Arbeitslosenversicherung; Kündigungsschutz; Arbeitsbeziehungen; Belgien